Impact of AI Technologies on Operations of Small and Medium Transport Businesses - Nicin, Vojislava; Nicin, Slobodan; Mirkov, Milovan (Communications - Scientific Letters of the University of Zilina, 2024)
In this article, the authors present a study on artificial intelligence (AI) integration in transportation and storage SMEs, focusing on research questions, literature reviews, hypotheses, sample selection, and data analysis. They explored current AI support and perceptions and plans of SMEs in this sector. The authors addressed the lack of literature on AI use in transport SMEs and investigated factors, such as AI adoption, benefits perception, company size correlation, and investment willingness. Data was collected from 163 SMEs in Serbia and Slovakia, revealing challenges in participant identification due to low AI use. Declining AI adoption rates authors attributed to financial, technological, regulatory, and awareness issues. The research aims to enhance the AI adoption in transportation and storage SMEs and give some directions for future work.
Keywords: artificial intelligence; small and medium enterprises; transportation; storage; logistics; perception; technology adoption